Urgensi Pemahaman Bahasa Ibu oleh Da’i dan Da’iyah dalam menyampaikan Dakwah di kalangan Remaja Masjid Jami’ Muhammad Jaya Di Kelurahan Sei Sekambing C II Medan - Risa Seskartini (MOUSE JURNAL HUMANIORA, 2025)
Mother tongue is a language that is used in a region in a country and is used for everyday speech by that community. the number of use of the mother tongue must be less than the total population in the country. If the number of speakers is more, then the language is the national language. The word language itself has a meaning, namely the ability of humans to say things to other humans either by using words, signs or body movements. Language is a tool or means to communicate between humans in the form of an information exchange system with sound symbols produced from human speech tools. Language is composed of thousands of words, each of which has a different meaning. Words represent an abstract relationship between a word and the object or concept represented by the word. A collection of words or vocabulary compiled by linguists in an alphabetical order and then compiled into a book called a dictionary or lexicon. This dictionary will later become a guide in learning the language in a standard and correct manner. In conveying everything, expressing opinions or ideas, humans cannot do it haphazardly. Humans must follow the rules of the language in which they are located so that the speech conveyed can be understood by the interlocutor. Indonesia is a country rich in language and customs. Indonesia has thousands of islands, and most of them have their own mother tongue. Even some regions have more than 1 mother tongue. For example, in Papua, which has more than 270 mother tongues. Mother tongue is often likened to the identity of the area. Local people can certainly speak their mother tongue. Even though in the modern era, Mother Language is rarely used, but it will be very good if it continues to be studied and passed on to posterity. If not, then the mother tongue and local customs will be lost due to changing times.